Gold nanoparticles supported on mesoporous iron oxide for enhanced CO oxidation reaction. Issue 10 (22nd February 2018) - Tanaka, Shunsuke; Lin, Jianjian; Kaneti, Yusuf Valentino; Yusa, Shin-ichi; Jikihara, Yohei; Nakayama, Tsuruo; Zakaria, Mohamed Barakat; Alshehri, Abdulmohsen Ali; You, Jungmok; Hossain, Md. Shahriar A.; Yamauchi, Yusuke
Abstract : Herein, we report the synthesis of gold (Au)-loaded mesoporous iron oxide (Fe2 O3 ) as a catalyst for both CO and NH3 oxidation. Abstract : Herein, we report the synthesis of gold (Au)-loaded mesoporous iron oxide (Fe2 O3 ) as a catalyst for both CO and NH3 oxidation. The mesoporous Fe2 O3 is firstly prepared using polymeric micelles made of an asymmetric triblock copolymer poly(styrene- b -acrylic acid- b -ethylene glycol) (PS- b -PAA- b -PEG). Owing to its unique porous structure and large surface area (87.0 m 2 g −1 ), the as-prepared mesoporous Fe2 O3 can be loaded with a considerably higher amount of Au nanoparticles (Au NPs) (7.9 wt%) compared to the commercial Fe2 O3 powder (0.8 wt%). Following the Au loading, the mesoporous Fe2 O3 structure is still well-retained and Au NPs with varying sizes of 3–10 nm are dispersed throughout the mesoporous support. When evaluated for CO oxidation, the Au-loaded mesoporous Fe2 O3 catalyst shows up to 20% higher CO conversion efficiency compared to the commercial Au/Fe2 O3 catalyst, especially at lower temperatures (25–150 °C), suggesting the promising potential of this catalyst for low-temperature CO oxidation. Furthermore, the Au-loaded mesoporous Fe2 O3 catalyst also displays a higher catalytic activity for NH3 oxidation with a respectable conversion efficiency of 37.4% compared to the commercial Au/Fe2 O3 catalyst (15.6%) at 200 °C. The significant enhancement in the catalytic performance of the Au-loaded mesoporous Fe2 O3 catalyst for both CO and NH3 oxidation may be attributed to the improved dispersion of the Au NPs and enhanced diffusivity of the reactant molecules due to the presence of mesopores and a higher oxygen activation rate contributed by the increased number of active sites, respectively.